WHY LEARNING FOREIGN LANGUAGES IS CRUCIAL FOR UZBEKISTAN - Buriyeva Charos Botirovna (Western European Studies, 2025)
In the context of the growing threats of a negative impact on the worldview of youth in the XXI century, the relevance of learning foreign languages is gaining special importance. Moreover, implies the establishment and intensification of bilateral cooperation in the field of education of higher educational institutions and representatives of public international organizations in order to increase the intellectual development of the younger generation. It should be noted that after Uzbekistan gained independence, the need to study foreign languages at a high communicative level in order to ensure security and stable development of the country's educational sphere was highlighted. At present, according to the world community Uzbekistan is actively cooperating with foreign partners in various directions, including in the field of education
Keywords: XXI century; foreign languages; education